Non-Markovian Corrections to Quantum Regression Theorem for the Strong Coupling Spin-Boson Model - Arzu Kurt (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
We report the results of an investigation of the effects of non-Markovian corrections to the dynamics of two-time correlation functions of the strong interaction spin-boson model. Beyond quantum regression theorem corrections are taken into account at the low environmental temperatures for a two-level system (TLS) which is in contact with a structured bath. The results indicate that the corrections lead to appreciable (small) quantitative (qualitative) differences for both biased and non-biased TLS settings.